Heterogeneous speculators and stock market dynamics: A simple agent-based computational model - Noemi Schmitt; Ivonne Schwartz; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
We propose a simple agent-based computational model in which speculators' trading behavior may cause bubbles and crashes, excess volatility, serially uncorrelated returns, fat-tailed return distributions and volatility clustering, thereby replicating five important stylized facts of stock markets. Since each speculator bets on his own (technical and fundamental) trading signals, stock prices are excessively volatile and oscillate erratically around their fundamental value. However, speculators' heterogeneity occasionally vanishes, e.g. due to panic-induced herding behavior, yielding extreme returns. Lasting regimes with high volatility originate from the fact that speculators extract stronger trading signals out of past stock price movements when stock prices fluctuate strongly. Simulations furthermore suggest that circuit breakers may be an effective tool to combat financial market turbulences.
Keywords: C63; D84; G15; 330; stock markets; stylized facts; agent-based computational models; technical and fundamental analysis; circuit breakers; econophysics